European consensus-based interdisciplinary guideline for melanoma. Part 1: Diagnostics – Update 2019 - Garbe, Claus; Amaral, Teresa; Peris, Ketty; Hauschild, Axel; Arenberger, Petr; Bastholt, Lars; Bataille, Veronique; del Marmol, Veronique; Dréno, Brigitte; Fargnoli, Maria Concetta; Grob, Jean-Jacques; Höller, Christoph; et al. (European journal of cancer (1990), 2020)
Cutaneous melanoma (CM) is potentially the most dangerous form of skin tumor and causes 90% of skin cancer mortality. A unique collaboration of multidisciplinary experts from the European Dermatology Forum (EDF), the European Association of Dermato-Oncology (EADO), and the European Organization of Research and Treatment of Cancer (EORTC) was formed to make recommendations on CM diagnosis and treatment, based on systematic literature reviews and the experts' experience. The diagnosis of melanoma can be made clinically and shall always be confirmed through dermatoscopy. If a melanoma is suspected, a histopathological examination is required. Sequential digital dermatoscopy and full-body photography can be used in risk persons to detect the development of melanomas at an earlier stage. Where available, confocal reflectance microscopy can improve clinical diagnosis in special cases. Melanoma shall be classified according to the 8th version of the AJCC classification. Thin melanomas up to 0.8 mm tumor thickness does not require further imaging diagnostics. From stage IB onwards, examinations with lymph node sonography are recommended, but no further imaging examinations. From stage IIC whole-body examinations with CT or PET-CT in combination with brain MRI are recommended. From stage III and higher, mutation testing is recommended, particularly for BRAF V600 mutation. It is important to provide a structured follow-up to detect relapses and secondary primary melanomas as early as possible. There is no evidence to support the frequency and extent of examinations. A stage-based follow-up scheme is proposed, which, according to the experience of the guideline group, covers the minimum requirements; further studies may be considered. This guideline is valid until the end of 2021.